EXPLORING OBSTACLES AND CHALLENGES IN THE PRACTICE OF TEACHING ARABIC AT MAWADDAH JUNIOR HIGH SCHOOL IN DEPOK - Zaidaan, Muhammad; Rivaldy, Daffa Achmad; Az Zaky, Sulton Hussain; Maswani (SHAWTUL ARAB, 2025)
Arabic holds a significant role in Islamic education, particularly at the junior secondary level in faith-based schools. Mastery of the language not only supports students’ linguistic competence but also deepens their understanding of Islamic teachings through religious texts. This exploration of Arabic language teaching practices at SMP Mawaddah, Depok, West Java, reveals various challenges faced by teachers and the strategies employed to overcome them. Using a descriptive qualitative approach, data were collected through direct classroom observations and semi-structured interviews. Key challenges include low student motivation and interest, limited instructional time, and diverse student backgrounds and proficiency levels. To address these obstacles, teachers implement personalized approaches, utilize simple and contextual learning media, enhance student motivation, and manage time efficiently. These findings offer a clear picture of the dynamics of Arabic language instruction in Islamic-based schools and encourage the adoption of more adaptive and effective teaching strategies.